Gravitational redshifts and the mass distributions of galaxies and clusters - Coggins, Simon John (2003)
This thesis studies a new method of constraining the mass distributions of elliptical galaxies and clusters of galaxies: gravitational redshift. The aim was to determine the types of astrophysical object in which gravitational redshift can be most readily detected and to attempt to observe the effect for the first time in a single object.